2010
DOI: 10.1108/00251741011043885
|View full text |Cite
|
Sign up to set email alerts
|

Internal and lateral communication in strategic alliance decision making

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The interorganizational exchange, combination and generation of resources, particularly knowledge, drive NPD in alliances (Grant and Baden-Fuller, 2004). These knowledge-transformation processes strongly depend on communication processes (Butler, 2010;Javidan et al, 2005). Communication describes the process of exchanging information between a sender and a receiver (Samovar et al, 2009).…”
Section: Divergent Communication Schemesmentioning
confidence: 99%
“…The interorganizational exchange, combination and generation of resources, particularly knowledge, drive NPD in alliances (Grant and Baden-Fuller, 2004). These knowledge-transformation processes strongly depend on communication processes (Butler, 2010;Javidan et al, 2005). Communication describes the process of exchanging information between a sender and a receiver (Samovar et al, 2009).…”
Section: Divergent Communication Schemesmentioning
confidence: 99%
“…However, in the last decade or so, academic and managerial thinking has moved from a predominant view of individual firms and transactions to one of interaction and networked firms pursuing long‐term relationships as illustrated by the large number of studies in alliances and relationship marketing (Pateli, 2009; Dilk et al , 2008; Teng and Das, 2008; Gulati, 2007, 1998; Möller et al , 2005; Ritter and Gemünden, 2003b). There are also studies, which propose the transition from interfirm dyadic relationships to strategic partnerships and networks (Butler, 2010; Rahman and Korn, 2010; Dodourova, 2009; Ploetner and Ehert, 2006; Ritter and Gemünden, 2003a; Ritter et al , 2002). This new perspective assumes that actors are embedded within networks of interconnected relationships that provide opportunities for learning and also constraint on their actions (Das and Kumar, 2010; Teng and Das, 2008; Brass et al , 2004; Ellis and Mayer, 2001).…”
Section: Inter‐firm Market Orientation (Imo)mentioning
confidence: 99%
“…This was consistent with the thinking and findings of others (Alpkan, Bulut, Gunday, Ulusoy, & Kilic, ; Arroyo‐Barrigüete, Ernst, López‐Sánchez, & Orero‐Giménez ; Fuentes Fuentes, Ruiz Arroyo, Bojica, & Fernández Pérez, ; Fuller‐Love, ; Hsueh, Lin, & Li, ; Pechlaner & Bachinger, ; Santos, ; Tolstoy, ). Importantly, however, when the firm pairings involved were confined to firms based in the same country, similarity of assets was more likely to be associated with alliances than M&As (Bras, Costa, & Buhalis, ; Butler, ; Das & Kumar, ; Dodourova, ; Lee, Liang, & Liu, ; Lowensberg, ; McLeod, Vaughan, & Edwards, ; Pateli, ; Rahman & Korn, ; Tjemkes & Furrer, ; Tsuchiya, ; Zehrer & Raich, ). Finally, when the firms were each based in different countries, Ortiz‐de‐Urbina‐Criado et al (this issue) showed that complementary of assets were associated with the use of alliances over M&As.…”
Section: The Content Of the Special Featurementioning
confidence: 99%